Assessment of air pollutant emissions from rice straw open burning in Hoa Vang district, Da Nang city, Vietnam - Nhu-Thuc Phan; Cu Dinh-Tri (Tạp chí Khoa học và Công nghệ)
This study inventoried the air pollutants from rice straw open burning (RSOB) in Hoa Vang district, Da Nang city, Vietnam. The rice straw in Hoa Vang district tended to decrease due to the shrinking rice cultivation area, of which 73% was reused in mushroom growing, livestock feeding, composting..., the remaining 27% was not reused and burned. The amount of rice straw burned in 2019 and 2023 was 25544 and 23377 tons, respectively. In 2023 the emissions of CO2, CO, PM10, PM2.5, SO2 and NO2 from RSOB were 27138, 1720, 509, 233, 25.9 and 11.4 tons/year, respectively. Burning conditions affected the air pollutant emissions from RSOB. At 5m from the burning site, the air pollutants were higher than the permissible standards, whereas at 200m from the burning site, the air pollutants decreased to the background concentration. These results are useful for both local and national environment managers in controlling air quality.